IMF Survey, Volume 35, Issue 07. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
2006 spring meetings preview; Reform at the IMF: Medium-Term Strategy; Global Financial Stability Report; World Economic Outlook: Oil and imbalances; Globalization and inflation; Puzzle of corporate saving; Profitable investment in Africa.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet